2020
DOI: 10.1136/jitc-2019-000340
|View full text |Cite
|
Sign up to set email alerts
|

ATR inhibitor AZD6738 enhances the antitumor activity of radiotherapy and immune checkpoint inhibitors by potentiating the tumor immune microenvironment in hepatocellular carcinoma

Abstract: BackgroundRadioimmunotherapy has a promising antitumor effect in hepatocellular carcinoma (HCC), depending on the regulatory effect of radiotherapy on tumor immune microenvironment. Ionizing radiation (IR)-induced DNA damage repair (DDR) pathway activation leads to the inhibition of immune microenvironment, thus impairing the antitumor effect of radioimmunotherapy. However, it is unclear whether inhibition of the DDR pathway can enhance the effect of radioimmunotherapy. In this study, we aim to explore the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 39 publications
2
113
0
Order By: Relevance
“…ATR inhibition potentiated type I IFN production in concert with IR in a cGAS–STING-dependent manner [ 97 ]. Moreover, ATR inhibition in combination with IR and immune checkpoint blockade resulted in superior antitumor efficacy in hepatocellular carcinoma models in a cGAS–STING-mediated manner [ 123 ]. As mentioned previously, one of the drawbacks of radiation-induced activation of the STING pathway is recruitment of immunosuppressive MDSCs to the TME [ 113 ].…”
Section: Augmenting Sting Signaling To Enhance Radiation-induced Amentioning
confidence: 99%
“…ATR inhibition potentiated type I IFN production in concert with IR in a cGAS–STING-dependent manner [ 97 ]. Moreover, ATR inhibition in combination with IR and immune checkpoint blockade resulted in superior antitumor efficacy in hepatocellular carcinoma models in a cGAS–STING-mediated manner [ 123 ]. As mentioned previously, one of the drawbacks of radiation-induced activation of the STING pathway is recruitment of immunosuppressive MDSCs to the TME [ 113 ].…”
Section: Augmenting Sting Signaling To Enhance Radiation-induced Amentioning
confidence: 99%
“…The immune microenvironment plays a positive and negative role in the occurrence, development and invasion of cancer. In general, the stronger the immune cell invasion in the tumor microenvironment, the more able to inhibit tumor progression [39][40][41][42]. There are three processes in the immune response of cancer: elimination, balance and escape.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that other DDR inhibitors, such as ATR, WEE1, and CHK1 inhibitors, have synergistic effects with immune checkpoint inhibitors. Sheng et al [150] demonstrated that AZD6738 enhances the efficacy of immune checkpoint inhibitors and radiotherapy in hepatocellular carcinoma. The synergistic antitumor effect of AZD6738 and radioimmunotherapy combination therapy depended on cyclic GMP-AMP synthase (cGAS)/STING signaling pathway activation.…”
Section: Ddr Inhibitors and Immune Checkpoint Inhibitorsmentioning
confidence: 99%